Leukoencephalopathies Associated with Macrocephaly - Renaud, Deborah L. (Seminars in Neurology, 2012)
Macrocephaly, enlarged head size, can be seen in a wide range of conditions including hydrocephalus and genetic syndromes. Benign familial macrocephaly may be seen in multiple generations and is not associated with neurologic concerns. When macrocephaly is seen in conjunction with abnormal white matter on neuroimaging, specific genetic leukoencephalopathies should be considered, including Alexander's disease, Canavan's disease, childhood ataxia with central hypomyelination/ vanishing white matter disease (CACH/VWMD), glutaric aciduria type I, L2-hydroxyglutaric aciduria, and megalencephalic leukoencephalopathy with subcortical cysts (MLC).
Keywords: leukoencephalopathy; leukodystrophy; macrocephaly; megalencephaly